2017
DOI: 10.1111/iju.13294
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy undergrading in men with Gleason score 6 and fatal prostate cancer in the European Randomized study of Screening for Prostate Cancer Rotterdam

Abstract: Part of the prostate cancer deaths with Gleason score ≤6 at prevalence screening in the European Randomized study of Screening for Prostate Cancer Rotterdam could be explained by biopsy undergrading. The present study confirms that the International Society of Urological Pathology 2014 modified Gleason score is more accurate for prognostic assessment based on prostate biopsy than the classical Gleason score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Recent reports showed that BCR in patients with latent GP5 was 57% at 5 years, which was almost equal to BCR of the high-risk group and 4+3+tertiary GP5 (5,15). Even if patients were diagnosed as having low-risk for PC, the Rotterdam randomized study of screening for PC showed that 15 patients out of 98 (15%) died of cancer (16). Primary GP4, >50% positive biopsy cores, or having more than one D'Amico intermediate-risk factor (i.e., stage cT2b, PSA levels of 10-20 ng/ml, or GS7) was known to be poor prognostic factors in the intermediate-risk group (17).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports showed that BCR in patients with latent GP5 was 57% at 5 years, which was almost equal to BCR of the high-risk group and 4+3+tertiary GP5 (5,15). Even if patients were diagnosed as having low-risk for PC, the Rotterdam randomized study of screening for PC showed that 15 patients out of 98 (15%) died of cancer (16). Primary GP4, >50% positive biopsy cores, or having more than one D'Amico intermediate-risk factor (i.e., stage cT2b, PSA levels of 10-20 ng/ml, or GS7) was known to be poor prognostic factors in the intermediate-risk group (17).…”
Section: Discussionmentioning
confidence: 99%
“…Demographic (age, body mass index, comorbidities), clinical (PSA, PSAD) mpMRI related (prostate weight, LD, lesion location), and pathological (biopsy International Society of Urological Pathology [ISUP] grade) data of all patients were evaluated. The pathological assessment of ≥ ISUP grade 1 was defined as PCa and ≥ ISUP grade 2 as csPCa [6]. PSAD was calculated as total PSA level (ng/mL)/prostate weight (cc).…”
Section: Methodsmentioning
confidence: 99%
“…In an elegant study, Alberts et al . has addressed these issues by allowing pathologists to blindly review biopsies with GS ≤6 and fatal cancer in the ERSPC cohort, together with other biopsies of non‐fatal cancer . They confirmed that the ISUP 2014 grading better predicts fatal disease, as 53% of fatal cancers were upgraded at biopsy review using contemporary criteria.…”
mentioning
confidence: 92%